PENGEMBANGAN MEDIA PEMBELAJARAN MAHᾹRAH QIRᾹ’AH DENGAN MENGGUNAKAN BOOK CREATOR - Taufik, Taufik; Rifki, Ahmad; Faiqotul Ilmiyah, Dina; Dinda Aghnia, Charity; Yani, Achmad; Murwanti, Murwanti (STIQ Amuntai, 2023)
With the rapid development of technology today, it is an opportunity for education to continue to innovate in creating an enjoyable learning environment. Conventional learning media has often become commonplace for students. Therefore, a breakthrough is needed in the form of web-based learning media. The method used in this research uses a type of research and development using the ADDIE (Analysis Design Development Evaluation) model. So, this research aims to develop Book Creator media to increase students' interest and motivation in studying Arabic and improve language skills; both Maharah Istima' wal Kalam and Qiro'ah wal Kitabah, which on this website have specifications in the form of input files, both text, images, audio, and video, which are arranged systematically to produce interactive learning media, so that the use of learning media using Book Creator is very feasible to develop. There are 23 steps in creating media using Book Creator. Still, there are only four steps in creating it, starting with creating a concept and preparing materials, then logging in, designing, and then distributing.